Widely targeted metabolomics reveals the antioxidant and anticancer activities of different colors of Dianthus caryophyllus - Zhou, Xuhong; Wang, Miaomaio; Li, Hong; Ye, Shilong; Tang, Wenru (Frontiers in Nutrition, 2023)
Carnation is edible flower that has potent antioxidant properties and is used in traditional chinese medicinal system and food industry. The phytochemicals responsible for these various proprieties, however, are not fully understood. Thus, in order to recognize metabolite diversity and variability in carnation flowers of different colors and to discover key metabolites that contribute to the differences in antioxidant and anticancer activities, widely targeted LC-MS/MS-based metabolomics analysis was conducteded on purple, green, yellow, and white carnation flowers. We identified and chemically categorized 932 metabolites. Metabolic compounds varied significantly with flower colour. Several flavonoids, organic acids, phenolic acids, and nucleotides and their derivatives were found to be specific differential metabolites in purple flowers. A total of 128 key differential metabolites were screened. The purple flowers were found to have the highest antioxidant and anticancer activities compared to the other colored flowers. Correlation analysis revealed that the 6-hydroxykaempferol-3,6-O-diglucoside, 6-hydroxykaempferol-7-O-glucoside, quercetin-3-O-sophoroside and 2'-deoxyguanosine were found to be the major constituents of the antioxidant and anticancer activities. 2' -deoxyguanosine has effective antiproliferative activity against A549 and U2OS cells for the first report. At the same time, the combination of 2' -deoxyguanosine with 6-hydroxykaempferol-3, 6-O-diglucoside or quercetin-3-O-sophoroside have also been found to increase the antitumor activity of 2' -deoxyguanosine. These discoveries enrich information on the phytochemical composition of carnation of different colors and provide resources for the overall use and improvement of carnation flowers quality.